2002
DOI: 10.1002/1615-9861(200205)2:5<486::aid-prot486>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

An improved formulation of SYPRO Ruby protein gel stain: Comparison with the original formulation and with a ruthenium II tris (bathophenanthroline disulfonate) formulation

Abstract: SYPRO Ruby protein gel stain is compatible with a variety of imaging platforms since it absorbs maximally in the ultraviolet (280 nm) and visible (470 nm) regions of the spectrum. Dye localization is achieved by noncovalent, electrostatic and hydrophobic binding to proteins, with signal being detected at 610 nm. Since proteins are not covalently modified by the dye, compatibility with downstream proteomics techniques such as matrix-assisted laser desorption/ionisation-time of flight mass spectrometry is assure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 38 publications
3
70
1
1
Order By: Relevance
“…The detection limit of protein in gels stained with SYPRO Ruby was in the order of 4 ng to 500 pg (Fig. 2a), which was in keeping with that found in other studies [2,8,9,22], and was an order of magnitude less sensitive than Lightning Fast. The high degree of speckling on the SYPRO Ruby gel was a concern and was therefore repeated but produced the same result.…”
Section: Performance Of Lightning Fast Protein Gel Stainsupporting
confidence: 90%
“…The detection limit of protein in gels stained with SYPRO Ruby was in the order of 4 ng to 500 pg (Fig. 2a), which was in keeping with that found in other studies [2,8,9,22], and was an order of magnitude less sensitive than Lightning Fast. The high degree of speckling on the SYPRO Ruby gel was a concern and was therefore repeated but produced the same result.…”
Section: Performance Of Lightning Fast Protein Gel Stainsupporting
confidence: 90%
“…Ruthenium (II) tris (bathophenanthroline disulfonate), RuBPS (also known as RuBPSA and RuBTS) was introduced as an economical alternative to SR in 2000 [162]. Although it was suggested that RuBPS delivered superior sensitivity in comparison to SR [163], it was later demonstrated that there was no quantitative advantage over the original or optimized SR formulation [164]. It is, however, definitely more cost-effective and has thus been used in various proteomic investigations [165][166][167][168][169][170].…”
Section: Non-reactive Fluorescent Dyesmentioning
confidence: 99%
“…It is, however, definitely more cost-effective and has thus been used in various proteomic investigations [165][166][167][168][169][170]. It has been shown that the limit of sensitivity of RuBPS is approximately 10 ng protein/band (broad-range MW standards, Bio-Rad), as reported previously [164] and determined qualitatively from published data [163]; however, a more detailed evaluation of RuBPS staining indicated this sensitivity threshold to be much lower, at ∼2 ng protein/band (CA, soybean trypsin inhibitor, OVA, albumin, PhosB) [168]. Similarly to SR, the LDR for RuBPS was between 2 and 2,500 ng for BSA [168].…”
Section: Non-reactive Fluorescent Dyesmentioning
confidence: 99%
“…The staining method was essentially according to Berggren et al 13 2-D gels were fixed after electrophoresis using 400 mL of a 10% MeOH/7% HAc solution for 1 h; fixing was not required for 1-D gel before staining. 1-D electrophoretic gels were placed into 50 mL (300 mL for 2-D gel) of a SYPRO Ruby staining solution for no less than 3 h. The gels were then rinsed briefly in a 10% MeOH/7% HAc solution for 30 min.…”
Section: Sypro Ruby Staining Protocolmentioning
confidence: 99%